A thermal stable pincer-MOF with high selective and sensitive nitro explosive TNP, metal ion Fe3+ and pH sensing in aqueous solution. (February 2020) - Wu, Ke; Hu, Jinsong; Shi, Shengnan; Li, Jiaxin; Cheng, Xiaofei
Abstract: A new 2D pincer-MOF [L4 Cd3 (H2 O)2 ] n (1 ) (H2 L = 1, 3-(bis(6-(2-methyl)nicotinyl))benzene) was synthesized by solvothermal method. In complex 1, each ligand links adjacent [Cd(COO)2 ] n chains to generate bi-layer 2D sheet. Emission spectrum reveals the fluorescence of complex 1 is mainly from the ligands to ligands charge transfer transition. Further investigation indicates that complex 1 can be employed as high selectively fluorescence sensor for detecting TNP and Fe 3+ in aqueous solution, the quenching constant ( K sv ) for TNP is 6.6 × 10 4 M −1 with the detection limit (LOD) of 0.119 μM; the K sv for Fe 3+ is 9.8 × 10 4 M −1 with the LOD of 0.095 μM. Besides, complex 1 has positive responses to pH values (pH = 2–3). Furthermore, the sensing mechanisms have been studied based on experiments and theoretical calculations. Highlights: A water and thermal stable luminescence pincer based metal-organic framework material was synthesized and characterized. Fluorescent sensing experiment exhibits complex 1 can selective detect TNP through noumenal fluorescence quenching effect. Complex 1 has high sensitivity for sensing Fe 3+ via weak interaction and noumenal flusorescence quenching effect. Complex 1 also has positive fluorescence responses to pH values (pH=2-3). The detection mechanisms and recyclability were studied based on both IR, XPS, titration and calculation.